2023
DOI: 10.1088/2040-8986/acb723
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pearcey beam with enhanced focusing effects

Abstract: In this paper, the focusing effects of the Pearcey beam (PB) are improved based on catastrophe optics, and the Pearcey integral is modified based on the butterfly catastrophe light field. A modified Pearcey beam (MPB) with a long focal depth is proposed, and the flexible adjustment of the focus position of the MPB is realized through theoretical analysis, simulation and experiment. The long focal depth of the beam is achieved under the premise of keeping the stable focus of the beam. Compared with the PB, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Focused beams can be used to manipulate small particles and improve the signal-to-noise ratio for free-space optical links [1,2]. Researches have shown that some beams have abrupt auto-focusing properties, such as circular Airy beams (CABs) [1,3], circle Pearcey beams [4,5], circle Olver beams [6], and so on [7][8][9]. It is worth mentioning that the CABs have attracted a lot of attention due to their auto-focusing property.…”
Section: Introductionmentioning
confidence: 99%
“…Focused beams can be used to manipulate small particles and improve the signal-to-noise ratio for free-space optical links [1,2]. Researches have shown that some beams have abrupt auto-focusing properties, such as circular Airy beams (CABs) [1,3], circle Pearcey beams [4,5], circle Olver beams [6], and so on [7][8][9]. It is worth mentioning that the CABs have attracted a lot of attention due to their auto-focusing property.…”
Section: Introductionmentioning
confidence: 99%